Modulation of the clinically accessible gelation time using glucono-d-lactone and pyridoxal 5′-phosphate for long-acting alginate in situ forming gel injectable - Kim, Hyungtaek; Song, Dahee; Ngo, Hai V.; Jin, Gang; Park, Chulhun; Park, Jun Bom; Lee, Beom Jin (Carbohydrate Polymers, 2021)
The purpose of this study was to design alginate in situ forming gel (ISFG) injectable with clinically acceptable gelation time and controlled release of hydrophobic drug. Milled or unmilled paliperidone palmitate (PPP) was used. The gelation time was controlled by varying the ratios of glucono-d-lactone (GDL) and pyridoxal 5′-phosphate (PLP) in prefilled alginate solution mixtures (ASMs) containing PPP, CaCO3, GDL and PLP for clinically acceptable injectability. However, the gelation time was varied by the alginate type (M/G ratio), storage condition, and drug solubilizers. This ISFG exhibited 32.15 kPa of the maximal compressive stress without causing pain and stiffness. The ISFG containing conically milled PPP released PPP in a controlled manner without exhibiting any initial burst release for 4 weeks. The current alginate ISFG injectable using new combination of PLP and GDL could be used to deliver long-acting injectable drugs.
Keywords: Clinically acceptable gelation time; Controlled release; Gelation time; Glucono-d-lactone; In-situ forming gels; Injectables; Paliperidone; Paliperidone palmitate; Particle size reduction; Pyridoxal 5' phosphates; Alginates; Chemical Phenomena; Delayed-Action Preparations; Gluconates; Humans; Hydrogels; Injections; Lactones; Microscopy, Atomic Force; Paliperidone Palmitate; Particle Size; Pyridoxal Phosphate; Clinically acceptable gelation time; Controlled release; Glucono-d-lactone; In situ forming gel; Paliperidone palmitate; Particle-size reduction; Pyridoxal 5′-phosphate